2014
DOI: 10.1177/1073191114533814
|View full text |Cite
|
Sign up to set email alerts
|

The Brief Irritability Test (BITe)

Abstract: Elevated levels of irritability have been reported across a range of psychiatric and medical conditions. However, research on the causes, consequences, and treatments of irritability has been hindered by limitations in existing measurement tools. This study aimed to develop a brief, reliable, and valid self-report measure of irritability that is suitable for use among both men and women and that displays minimal overlap with related constructs. First, 63 candidate items were generated, including items from two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 66 publications
(108 reference statements)
4
100
0
Order By: Relevance
“…Diener et al 2009 ), and irritability (cf. Holtzman et al 2015 ). A 2 (group) × 2 (time) repeated measures ANOVA revealed a main effect of time ( F (1,67) = 63.1, p < 0.001) for the personal vulnerability subscale of the SOS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diener et al 2009 ), and irritability (cf. Holtzman et al 2015 ). A 2 (group) × 2 (time) repeated measures ANOVA revealed a main effect of time ( F (1,67) = 63.1, p < 0.001) for the personal vulnerability subscale of the SOS.…”
Section: Resultsmentioning
confidence: 99%
“…Diener et al 2009 ), and the BITe (cf. Holtzman et al 2015 ). Thus, although previous studies suggest that mindfulness is effective at reducing symptomatology and improving well-being in patient populations (Hofmann et al 2010 ; Reibel et al 2001 ), caution should be applied when attempting to extrapolate the findings reported here to other cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEER-9 serves as a tool for quantifying the prevalence of emotional dysregulation in children and youth. Recently, irritability scales have been developed and validated for women ( Born, Koren, Lin, & Steiner, 2008 ) and adults ( Craig, Hietanen, Markova, & Berrios, 2008 ), including one using IRT ( Holtzman, O’Connor, Barata, & Stewart, 2015 ). CEER-9 will allow researchers to better understand the developmental course of emotional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The present results suggest that measures differ in their conceptualisation and measurement of irritability. Although multi-item irritability measures such as the Irritability Questionnaire have been shown to have good reliability and assess various thoughts, feelings and behaviours related to irritability, scales attempting to measure irritability also tap into constructs such as anger and hostility (Holtzman, O'Connor, Barata & Stewart, 2015). This may be problematic in the assessment of irritability since irritability, unlike anger, often occurs in the absence of a direct antecedent and lasts longer, suggesting that they are different constructs which require differentiation in assessments (Beedie et al, 2005;Craig et al…”
Section: Accepted Manuscriptmentioning
confidence: 99%